2009
DOI: 10.1111/j.1439-0272.1990.tb02085.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretory proteins of human seminal vesicles and their relationship to lipids and sugars: Sekretorische Proteine der menschlichen Bläschendrüse und ihre Beziehungen zu Lipiden und Zuckern

Abstract: Proteins secreted by human seminal vesicles are strongly positively charged. Cellulose acetate electrophoresis show how the presence of two protein bands of vesicular origin (N3 and N4). When studied on SDS-PAGE there are three main bands of molecular weight 67,45 and 40 kDa, respectively. These proteins may be separated by a chromatographic process using gel filtration on Sephadex G 25 M and ion exchange chromatography on CM and SP Sephadex C 50. Fructose, secreted by seminal vesicles, is excreted with specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In addition, the triacylglycerols, glycerol tripropanoate and 2,3-diacetoxypropyl stearate, were accumulated in HF bulls. It was previously demonstrated that sperm can utilize triglycerides for their metabolism [55,56]. It is known that seminal plasma contains cholesterol and triacylglycerols, the latter serving as energy sources [57].…”
Section: Metabolomic Analysis Of Seminal Plasma From Hf and Lf Bullsmentioning
confidence: 99%
“…In addition, the triacylglycerols, glycerol tripropanoate and 2,3-diacetoxypropyl stearate, were accumulated in HF bulls. It was previously demonstrated that sperm can utilize triglycerides for their metabolism [55,56]. It is known that seminal plasma contains cholesterol and triacylglycerols, the latter serving as energy sources [57].…”
Section: Metabolomic Analysis Of Seminal Plasma From Hf and Lf Bullsmentioning
confidence: 99%